SCRUTINIZATION OF THE IMPLEMENTATION OF THE CURRICULUM MERDEKA IN ELEMENTARY SCHOOLS: A LITERATURE REVIEW - Deni Yuliani; Eka. Supriatna; Henny Sanulita; Elva Refariza; Dwi Hadita Ayu; Wily Mohammad (Consilium: Education and Counseling Journal, 2023)
The study aims to scrutinize the implementation of the Curriculum Merdeka in elementary schools. The type of research used in research is qualitative research, namely research that does not use quantitative data or statistical measurement tools. Under the object of this thesis, this type of research is in the category of library research (library research), namely a series of studies using library research. The Curriculum Merdeka also supports project-based learning strategies. Through this strategy, students are expected to be able to apply the material learned through projects and case studies. Later, the projects and case studies carried out by students will be known as the Strengthening Pancasila Student Profile Project. The project is implemented so that students can achieve the Pancasila Student Profile. The Pancasila student profile itself is a character and ability that is built in everyday life and exists within every student. This includes faith and devotion to God Almighty, global diversity, cooperation, creativity, independence and the quality of critical reasoning. Pancasila student profiles can be built through educational cultural institutions, curricular learning, Pancasila student profile improvement programs, and extracurricular activities. The implementation of independent elementary school level courses prioritizes project-based learning to achieve the Pancasila student profile. This is also very relevant to learning in the 21st century, where learning does not only focus on knowledge but also emphasizes the acquisition of character, literacy, skills and technology. Independent study will again be subject-based.